Analisis Kandungan Hidrokuinon Pada Krim Pagi, Krim Malam yang Beredar di Online Shop - Odilia Dea Christina; Rosiana Putri Rahayu (Unit Penelitian dan Pengabdian Masyarakat Politeknik Kesehatan Bhakti Mulial, 2023)
Morning cream is a type of face cream that is used in the morning and night cream is specifically designed to repair skin cells while sleeping. Many mornings and evenings are sold through onlineshopp with a quick brightening effect. The content in facial whitening creams that usually can give a white effect is hydroquinone. Use of hydroquinone. The purpose of this study was to find out whether there is a hydroquinone content in night creams sold in online shops. Qualitative test results using TLC from 6 samples of morning and evening creams used, all samples containing hydroquinone. There were 4 samples of morning and night cream containing hydroquinone with levels in Cream A (morning) containing 3.360% hydroquinone, cream B (morning) containing 3.49% hydroquinone, cream B (night) containing 2.49% hydroquinone, and cream C (night) containing 2.92% hydroquinone is not in accordance with BPOM regulations because it exceeds 2%. There were 2 samples of morning and night cream containing hydroquinone with cream A (night) content of 0.948% and cream C (morning) 1.47% which did not exceed BPOM regulations or did not exceed 2%.